The impact of different types of social media influencers on university students' achievement motivation: a case study of university students at UTAR Sungai Long campus, Malaysia. - Yang , Yang (2024)

(untitled)
This study employed quantitative research methods within the framework of Social Cognitive Theory, focusing on students at the Sungai Long campus of Universiti Tunku Abdul Rahman in Malaysia to explore the impact of different types of social media influencers on university students’ achievement motivation, attitudes, and behaviours. Utilising multiple-choice questions, Likert scales, and the Achievement Motivation Scale (AMS), this research assessed the influence of different types of social media influencers (academic, career, social, and skill) on students’ values and achievement motivation.